Building the measure of the coherence of space organization as a social phenomenon - Bahjat Rashad Shahin; Wadah Abdu lSaheb Al-Musouy (Iraqi Journal of Architecture and Planning, 1970)
The sequence of values and sociality labilies fill with meanings and sample, and itsreflects the nature ofreaotion between a man and nature, because man doesn't part his urbainand Social nature from each other.From that, we can considered the spatial organization as a social phenomena, becauseit's more than collecting spatials, but it's represent a social fact, it's an Expression oftheSocial behavior for persons and groups who live it.So in Spatial organization we can see the bond between each person, and we candinguses the Social relations, and we oan see the Social problem through it.And although of the previous studies and researches as considered that Social fact, butit's still very limited, and in fact we can considered that the urbain design for the Spatialorganization type for the urbain nature, can be considered as animaginery process lor whatkind ofreaction should be taken place between man and nature.